An Examination of Tourists’ Optimal Telepresence Experience at a Heritage Site: Scale Development and Its Cascading Impacts - Doan, Thi Thanh Thuy (Auckland University of Technology, 2025)
Virtual reality (VR) is a state-of-the-art concept often considered a contemporary topic in the realm of tourism, especially for tourism marketing, which offers immersive and interactive experiences that stimulate real-world environments in users. Tourist destinations have been created in the virtual world to facilitate tourist interaction within virtual environments. This technology allows researchers to investigate tourist behaviour and decision-making processes within mediated environments, eliminating the need for physical travel. As a result, virtual reality provides marketers with a powerful tool to showcase virtual tours or promotional products that align with consumer intentions. A key concept in virtual reality is telepresence, which describes the sensation of being physically present in a virtual environment. Numerous studies have focused on factors that enhance the immersive experience, which leads to stronger feelings of telepresence, with many focusing on how telepresence impacts users’ potential travel destinations. However, there has been limited exploration of users’ VR experiences at physical sites, particularly heritage sites, with most prior research focusing on user’s VR and telepresence experiences in remote settings. Based on a systematic review of telepresence experiences in VR, and their impact on human behaviour conducted during the initial stages of this research, three main gaps were identified. These gaps underscore the necessity of conducting this empirical research. Specifically, the COVID-19 pandemic served as a catalyst for an increased number of studies on VR and telepresence, with the aim being to eliminate physical distance. While the pandemic is now largely under control, this study sought to investigate the effects of VR experiences at heritage sites, providing a deeper understanding of tourists’ psychological responses. With this aim, the contribution of this PhD research is to contribute to the understanding of tourists’ broad intentions when using VR in tourism (including heritage tourism). In particular, this research conceptualised a new term, ‘optimal telepresence experience’ (OTE), to elucidate the simultaneous virtual and physical travel experiences of VR users. This current empirical study was conducted at a heritage site in Vietnam, the Imperial City of Huế, which has VR devices installed. In 1993, UNESCO designated this largest structure in modern Vietnamese history, as a World Heritage Site. The heritage site’s VR devices allow on site tourists to travel back 200 years and explore the area when relics were still present. This study reveals that virtual users gain an optimal on-site experience, as opposed to a remote one. Grounded in principles relating to Flow Theory and telepresence, it highlights the importance of conceptualising OTE. The study adopted a post-positivist paradigm with a sequential mixed-methods approach. By using sequential exploration study, two studies were conducted with the aim of empirically examining the impact of OTE on tourists at the heritage site. The first study involved a semi structured interview with 28 participants (14 international and 14 domestic tourists). NVivo 26 was applied for the thematic analysis and coding. The qualitative findings revealed three themes that guided the conceptualisation of the ideal telepresence experience. After the conceptualisation of OTE, the second study validated the OTE construct by gathering 484 tourists (257 domestic and 227 international) who used VR at the heritage site. The first study identified three main attributes of OTE; emotional, cognitive, and functional, and concluded by confirming the definition of the new concept, ‘optimal telepresence experience’, contributing a new term to the discipline of investigating VR experience. The research findings showed that tourists who used VR technology at the heritage site had an OTE that was stronger than their physical visits alone. The reason being that they could ‘travel back’ to view the missing relics and enhance their engagement with the site. This study contributes to an understanding of how to optimise a heritage site’s VR device to trigger the users’ emotions in the mediated environment, to align with the site’s actual environment. Once tourists have completed their travel in the virtual world, they will easily connect with their physical environment and perceive their experience to be more meaningful. The second study created and validated the development of OTE scale items that can be used for future studies. These scale items were used for hypotheses testing and model measurement. The results demonstrated the significance of scale items via second-order model testing, which guaranteed the validity for hypotheses testing. The hypotheses testing and model measurement contributed valuable outcomes. Stimulus-Organism-Response (SOR) theory was used as a framework at this stage. First, it identified the role of existential authenticity (EAUTH) as a mediator in the relationship between OTE and tourist intention. Second, the research also revealed that cultural identity can change the extent of tourists’ experiences at a heritage site. In particular, international tourists with weaker cultural identity found it easier to participate in the trip than other tourist groups. The impact of tourists’ cultural identity on their OTE and subsequent intentions was a crucial aspect of the analysis. This is the first research to develop a new construct of tourists’ virtual reality experiences at heritage sites. It enhances the understanding of human interaction through the virtual world, especially for those who are at heritage sites. This research, through the application of SOR theory, offers a fresh viewpoint on the role of virtual experiences at physical sites, enabling users to fully appreciate the history of a site, particularly in light of a site’s destruction due to external factors.